The role of occlusion and occlusal adjustment on temporomandibular dysfunction - Gustavo Augusto Seabra Barbosa; Cândido dos Reis Badaró Filho; Rodrigo Borges Fonseca; Carlos José Soares; Flávio Domingues Neves; Alfredo Júlio Fernandes Neto (Universidade Estadual de Campinas, 2015)
There is a great controversy related to the role of occlusion and its usage on occlusal adjustment as a treatment of temporomandibular disorders. Occlusal adjustment is a clinical procedure in which modifications are done on teeth surfaces, restorations or prostheses, through selective wear or restorative materials addition, seeking to harmonize maxillo-mandibular functional aspects in centric occlusion and eccentric movements. The adjustment aims to obtain appropriate jaw stability free from premature contacts and occlusal interferences. The aim of this paper is to elucidate the role of occlusion and occlusal adjustment in Temporomandibular Dysfunction and to guide the professional when indicating it.